Atypical phase behaviour of quinoa protein isolate in mixture with maltodextrin. (December 2022) - Campos Assumpção de Amarante, Marina; MacCalman, Thomas; Harding, Stephen E.; Spyropoulos, Fotis; Gras, Sally; Wolf, Bettina
Graphical abstract: Highlights: Phase diagrams of quinoa protein isolate (QPI)-maltodextrin (MD) were constructed. Binodals shifted away from both axes with increasing concentration. Micrographs show a percolated protein network. Depletion flocculation proposed as the phase separation mechanism. QPI pre-heating and absence of salt did not change the phase separation mechanism. Abstract: Consumers are increasingly looking for new plant-based alternatives to substitute animal proteins in their diets but for some applications it can be difficult to achieve the desired product microstructure using only plant proteins. One approach to facilitate structuring is to mix these plant-based ingredients with a polysaccharide. Here, the phase behaviour and microstructure of quinoa protein isolate (QPI) in mixture with maltodextrin (MD) of two dextrose equivalents (DE 7 and 2) were investigated. The binodals of both QPI-MD phase diagrams showed an atypical shape, where the concentration of MD in the QPI-rich phase and of QPI in the MD-rich phase increased with overall biopolymer concentration. Molecular weight distribution and microstructure analyses revealed that both maltodextrins fractionated between the phases and were probably entrapped within the volume-spanning protein network in the QPI-rich phase, indicating a depletion flocculation mechanism of phase separation. The pre-heating of QPI and the removal of salt from the systems resulted in similarly atypical phase diagrams. The approach presented contributes to our understanding of the phase behaviour of mixtures between plant proteins and polysaccharides, while the results suggest that the formulation of plant-based products of predictable properties may be more challenging than anticipated.